Effect of different fabrication methods on the chemo-physical properties of silk fibroin films and on their interaction with neural cells. Issue 11 (22nd January 2016) - Sagnella, Anna; Pistone, Assunta; Bonetti, Simone; Donnadio, Anna; Saracino, Emanuela; Nocchetti, Morena; Dionigi, Chiara; Ruani, Giampiero; Muccini, Michele; Posati, Tamara; Benfenati, Valentina; Zamboni, Roberto
Abstract : In this study, we investigated the influence of processing methods on the chemo-physical properties of silk fibroin (SF) film and on their interaction with neural cells. Abstract : In this study, we investigated the influence of processing methods on the chemo-physical properties of silk fibroin (SF) film and on their interaction with neural cells. Structural, thermal and morphological analysis revealed a strong correlation between the conformation, stability and texture of silk films and the fabrication conditions. An increase in temperature, methanol treatment and the use of a microfluidic approach led to an improvement in SF film stability in terms of β-sheet content, mechanical resistance, dissolution and enzymatic degradation. An effect on the interaction of SF films with neural cells, through a modulation of the surface properties, was also observed. In particular, hydrophobic surfaces induce proliferation of astrocytes and neuron adhesion whereas hydrophilic surfaces promote a remarkable neurite outgrowth. A detailed knowledge of the effect of manufacturing parameters on SF film properties can facilitate and extend the applications of silk-based biomaterials in tissue engineering and drug release systems.